PERANCANGAN BUKU KOMIK DENGAN TEKNIK DIGITAL TENTANG MENGATASI STRES PADA DEWASA AWAL SEBAGAI UPAYA MENINGKATKAN MOTIVASI - Budiarti, Kurnia Octaviani; Budiardjo, Hardman; Patricia, Florens Debora (Jurnal Art Nouveau, 2018)
Stress is a condition that makes the individual feel depressed because of the pressure or burden demands. Psychosocial factors such as lost someone loved and the pressure from around make a persons not be able to enjoy their life. When a person can’t hold their stress, the worst consequence is the depression. Young adult is time when they enter the new live value and adaptation to new living. Failure to manage the problem when in young adult will effect on their self-adjustment that will be makes they have low self-esteem, closed person, and depression. According from WHO (World Health Organization) on “World Health Day” 2017, depression is the second deadly disease after cardiovascular. In the Riskesdas’s data of 2013 also show the prevalence of emotional mental disorder or depressive symptoms in Indonesia by 6% that occurred at the age of 15 years and above. For that reason, this research takes theme about mental illness with the topic about stress on young adult to make a comic book with digital techniques. This comic book will be contains about how to cope with stress with Mindfulness activities. Presented into a slice-of-life story about psychosocial problem on young adult. This research hope can be alternate for persons who look a book how to cope stress with different format.